Who Are Afraid of Losing Their Jobs to Artificial Intelligence and Robots? Evidence from a Survey - Masayuki Morikawa (Global Labor Organization (GLO), 2017)
This study, using original survey data of 10,000 individuals, analyzes the possible impacts of artificial intelligence (AI) and robotics on employment. The first interest of this study is to ascertain, from the viewpoint of workers, what types of worker characteristics are associated with the perception of risk of jobs being replaced by the development of AI and robotics. The second interest is to identify, from the viewpoint of consumers, what types of services are likely to be replaced by AI and robotics. The results suggest that malleable/adaptable high skills acquired through higher education, particularly in science and engineering, are complementary with new technologies such as AI and robotics. At the same time, occupation-specific skills acquired by attending professional schools or holding occupational licenses, particularly those related to human-intensive services, are less likely to be replaced by AI and robotics.
Keywords: J24; O33; D12; 330; artificial intelligence; robotics; skill; household production